Alisol A Alleviates Arterial Plaque by Activating AMPK/SIRT1 Signaling Pathway in apoE-Deficient Mice - Wang, Ke; Zhang, Beibei; Song, Dingzhong; Xi, Jianqiang; Hao, Wusi; Yuan, Jie; Gao, Chenyu; Cui, Zhongbao; Cheng, Zhihong (Frontiers in Pharmacology, 2020)
Alismatis Rhizoma (zexie), an herb used in traditional Chinese medicine, exhibits hypolipemic, anti-inflammation and anti-atherosclerotic activities. Alisol A is one of the main active ingredients in Alismatis Rhizoma extract. In this study, we investigate the role of alisol A in anti-atherosclerosis. Our study demonstrated that alisol A can effectively inhibit the formation of arterial plaques and blocked the progression of atherosclerosis in ApoE -/-mice fed with high-fat diet. and significantly reduced the expression of inflammatory cytokins in aorta, including ICAM-1, IL-6 and MMP-9.